A CAIC (Companhia de Agricultura, Imigração eColonização) e o processo imigratório no Estado de São Paulo (1928-1961) - Oliveira, Giani Vendramel de (2010)
This study aims to make a analysis of the performance of the Companhia de Agricultura, Imigração e Colonização (CAIC) in the State of São Paulo. Founded in July 1928, the Company had a major interest for the purchase of land, its shredding and sale of lots, as well as the introduction of agricultural workers, domestic and foreign, in the State of São Paulo. In October 1934 the company was reorganized to read as principal shareholder and "controlling" the Company Paulista de Estrada de Ferro. After thirty-three years of work to CAIC leave to exist as a private company in 1961 when, together with the Company Paulista was encamp by the Government.